Bile Nephropathy in Flucloxacillin-Induced Cholestatic Liver Dysfunction - Basil Alnasrallah; John F. Collins; L. Jonathan Zwi (Case Reports in Nephrology)
Kidney injury in the context of cholestatic liver dysfunction is not uncommon; this has been historically referred to as cholemic nephrosis implying a direct deleterious renal effect of cholemia. However, scepticism about the exact role that bile and its constituents play in this injury has led to the disappearance of the term. We describe a case of severe AKI due to bile nephropathy with bile casts in flucloxacillin-induced liver dysfunction. We also discuss the recent literature reviving the concept of bile nephropathy.